Hybrid multi-criteria decision making approaches for transtibial prostheses socket material selection - Tarun Rijwani; Gurusharan Dumra; Kumar Abhishek; Ganesh Iyer (Discover Applied Sciences)
Abstract The selection of appropriate material for manufacturing of prosthetic socket is a critical decision that impacts comfort, durability, functionality, and cost effectiveness. This study employs a comprehensive Multi Criteria Decision Making (MCDM) approach to evaluate ten potential materials for prosthetic sockets based on six evaluation criteria. High density polyethylene (HDPE), polypropylene (PP), nylon 6 (Polyamide 6), nylon 12 (Polyamide 12), polyethylene terephthalate (PET), unsaturated polyester resin, epoxy resin, vinyl ester resin, carbon fiber reinforced polymer (CFRP), and polylactic acid (PLA) are assessed based on density, specific compressive strength, yield strength, young’s modulus, thermal conductivity, and relative cost of material. To address the complexity and multi dimensionality of the material selection process, four different MCDM techniques, Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS), Multi Objective Optimization by Ratio Analysis (MOORA), Evaluation Based on Distance from Average Solution (EDAS), and Grey Relational Analysis (GRA) are employed in combination with an entropy weighting method to account for the varying importance of the criteria. By comparing these methods, we identify carbon fiber reinforced polymer (CFRP) and vinyl ester resin as most promising materials that balances the mechanical properties, thermal behaviour, and economic considerations. CFRP being most expensive material among peers, its remarkable mechanical properties make it outperform other materials. The findings serve as a comprehensive guide for researchers and practitioners in selecting materials to meet specific requirements for prosthetic socket manufacturing, while also offering a robust framework for future research and application in the field of prosthetics.